Cross-cultural encounters of Italian travellers in the Malay world; A perspective on the languages spoken by the local populations - Soriente, Antonia (Wacana, Journal of the Humanities of Indonesia, 2024)
This paper describes the encounters that Italian travellers, explorers, and traders had with the peoples of the Malay world at the turn of the century. In particular, it focuses on the linguistic descriptions and observations made by Italian explorers of the languages spoken in the places they visited and included in their travel writings. In addition to the pioneering work of Pigafetta, the Italian scribe who followed Magellan on his voyage around the world and produced the first “Italian-Malay vocabulary” in 1521, other linguistic descriptions and observations were made by Giovanni Gaggino, a merchant who compiled an Italian-Malay dictionary in Singapore, Odoardo Beccari, a naturalist who offered reflections on the Malay spoken in Borneo, and Celso Cesare Moreno, a ship captain and adventurer. Elio Modigliani, in his travels to Nias, Enggano, Mentawai, and the Batak country, provided detailed information on the local languages spoken in these islands in North and West Sumatra, while Giovanni Battista Cerruti, an explorer and ship captain who visited Singapore, Batavia, and the Malay Peninsula, commented on the languages, as did Emilio Cerruti, who travelled to the Moluccas and Papua. This paper focuses on how these languages were described and perceived by these nineteenth-century Italian travellers. It concludes that these explorers were all united by a common necessity, namely the importance of speaking local languages in order to be able to interact with the people they met on their travels. Malay, in particular, was always viewed positively as an international language, a powerful tool for communicating, learning, and interacting with others, and a beautiful language. Conversely, the other minority languages were seen as poor and simple, but still a powerful tool to overcome barriers and lay the foundations for intercultural communication.